PENINGKATAN HASIL BELAJAR JARING-JARING BALOK DAN KUBUS DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) BAGI SISWA KELAS IV SD NEGERI 02 LIMBANANG - Pratama, Fitra; Masniladevi, Masniladevi; Zen, Mulyani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of the research is to describe the student’s result in studying beam and cube webs with cooperative learning type Team Assisted Individualization (TAI) for fourth grade primary school of 02 Limbanang. The kind of the research is Classroom action research that use qualitative and quantitative approaches. The subject of this research are the teacher and 20 students of the fourth grade. The result of this research is to show of the increasing of the plan, process, and result of study. In conclusion, cooperatice learning type TAI  can increase the student’s result in studying beam and cub webs.Keywords: Studying Beam and Cub Webs, TAI